A new dialogue between biblical scholarship and Religious Education. Issue 3 (2nd September 2018) - Docherty, Susan
ABSTRACT: Religious Education (RE) naturally draws on various aspects of the academic study of religions to ensure the accuracy and currency of its content and pedagogy. This paper sets out the case for a more intense dialogue between RE and the field of biblical studies, in order to address perceived weaknesses in the teaching of Christianity in UK schools, specifically in the use of biblical material in the classroom. Two recent major shifts within biblical scholarship are highlighted here: (1) a transformation in the understanding of the first century Jewish context within which Christianity was formed and (2) the emergence of new forms of biblical interpretation which draw on the perspectives of previously marginalised groups. These developments potentially have important and positive implications for RE, because they demonstrate the breadth and variety of the religions of early Judaism and Christianity; offer new information about central topics on current RE syllabi; raise questions about the plurality and 'ownership' of the interpretation of sacred texts; encourage greater nuance in applying biblical texts to contemporary theological and ethical debates; and provide space for people from varied backgrounds to engage directly with the biblical texts in informed and innovative ways.